SOME POSSIBLE INNOVATIVE DIRECTIONS FOR FURTHER IMPROVEMENT OF LIFELONG PROFESSIONAL MEDICAL EDUCATION IN UZBEKISTAN - D.A. Asadov (The Bioscan, 2024)
the article analyzes the state, place and significance of training, retraining and continuous professional development of medical personnel in the effectiveness of the current stage of reforming the health care system of the Republic of Uzbekistan. Based on the nature of the ongoing reforms, taking into account the experience of countries with a developed healthcare system, partnership mechanisms and division of responsibilities in this area between the state and professional communities are proposed.